Phylogenetic trees made easy
Phylogenetic Trees Made Easy A How To Manual - Phylogenetic Trees Made Easy helps beginners get started in creating phylogenetic trees from protein or nucleic acid sequence data. Although aimed at molecular and cell biologists who may not be familiar with phylogenetic or evolutionary theory, it also serves students who may be familiar with phylogenetic theory but are unfamiliar with the tools used to apply that theory. The reader is led, step by step, through identifying sequences that are homologous to a sequence of interest, downloading these sequences from databases, creating multiple alignments and using several different methods to construct trees. Key changes to the Second Edition include: content and screen shots have been updated to reflect current software versions new Advanced Topics to extend understanding detailed discussion of PAUP as well as inclusion of PHYLIP as an alternative. Every copy of the Second Edition also includes a CD with current Windows and Macintosh beta versions of PAUP .